In-silico receptor interactions, phytochemical fingerprint and biological activities of Matricaria chamomilla flower extract and the main components - Burhanettin Sertaç Ayhan; Emine Yalçin; Kültiğin Çavuşoğlu (Scientific Reports)
Abstract In this study, total phenolic and flavonoid content, quantitative phenolic analysis, in-vivo, in-vitro and in-silico biological activities of Matricaria chamomilla flower extracts collected from Bulancak (Giresun) were investigated. Phenolic content was determined by LC–MS/MS and antioxidant, antibacterial, antifungal, antigenotoxic and anti-inflammatory activities of the extract and the main components were investigated. Caffeic acid, quercetin and kaempferol were detected as major compounds in the flower extract by LC–MS/MS analysis and the detected levels were 165.085 mg/kg, 112.673 mg/kg and 67.417 mg/kg, respectively. The DPPH radical scavenging activity of M. chamomilla flower extract ranged from 12.4 to 81.1%, while superoxide anion inhibition was observed between 10.6 and 65.8%. Even at low doses, the main components, caffeic acid, quercetin and kaempferol, alone show more potent antioxidant activity. Flower extract was effective against both gram-positive, gram-negative bacteria and fungi and exhibited a broad spectrum antimicrobial effect. Three main components showed a lower sidal effect than the flower extract. M. chamomilla flower extract showed significant antigenotoxicity by reducing NaN3-induced micronucleus formation by 58%, while the main components showed a lower activity. M. chamomilla flower extract, showed a protein denaturation inhibition in the range of 23.5% to 71% and its IC50 value was 408 µg/mL. The IC50 values of caffeic acid, quercetin and kaempferol, which are the main components of flower extract, were calculated as 306 µg/mL, 283 µg/mL and 333 µg/mL, respectively in anti-inflamatory test. The interactions of main components of M. chamomilla flower extract and GABAA receptor was investigated by in-silico molecular docking method. The interaction of caffeic acid, one of the main components detected in the extract, with GABAA was predominantly through hydrogen bonding and the binding energy of this interaction was − 5.01 kcal/mol. In the interaction between gentisic acid and GABAA, an inhibition constant of 351.67 µM was determined. The binding energies obtained in the kaempferol and quercetin interactions were − 5.47 kcal/mol and − 4.41 kcal/mol, respectively. The low/medium binding energies observed for the tested active ingredients indicate that other constituents in M. chamomilla flowers might exert stronger GABAA inhibition than the compounds evaluated. Additionally, weaker binding typically results in reversible interactions, which can be advantageous in certain therapeutic strategies. As a result, this study provides significant contributions to scientific knowledge in terms of reflecting regional diversity in the biological effects of M. chamomilla flower, comparative analysis of extracts and pure components, investigation of antigenotoxic activity on a component basis, and obtaining mechanistic evidence on sedative effect potential.